Development of Video-Based Learning Media for Learning Basic Passing and Control Techniques in Sawan 1 State Midlle School Football Games - I Gede Verry Yasa; I Made Satyawan; Peby Gunarto (Universitas Pendidikan Ganesha, 2024)
In the initial observation based on the needs analysis, it can be seen that learning video media is indispensable for basic passing and control techniques in football games. The research developed learning media based on learning videos using the ADDIE model, where the research subject was grade VIII SMP Negeri 1 Sawan. The results of data analysis on the development of learning video-based learning media were tested by experts and obtained an expert assessment of 86% of the content/learning materials in the good category, 92.5% of the assessment of learning design experts in the very good category, 91.6% of the assessment of learning media experts in the very good category and 96% of the assessment of field practitioner experts in the very good category. The small group trial received a rating of 96.4% in the very good category and the large group trial received a score of 96.8% in the excellent category. From these results, it can be concluded that learning video-based learning media is developed suitable for application in learning.